A method for preparing a carbon-supported NiCoMn@(αNiCoMn)SeJanus low-entropy alloy-medium-entropy metal selenide heterojunction catalyst

CN121372449BActive Publication Date: 2026-10-30QINGDAO UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511751327.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-26
Publication Date
2026-10-30
Estimated Expiration
2045-11-26

AI Technical Summary

Technical Problem

但是该方法分离纯度低,尤其是正极材料中可能混入铜、铝杂质,后续需二次提纯才能复用,并且对电池结构依赖性强,面对叠片式、软包式等复杂结构电池时,破碎和分选效果差,适用性有限,电解液处理难度也较大,物理过程无法有效去除电解液中的锂盐和有机成分,易导致电解液泄漏并造成污染

Benefits of technology

(1)废旧三元锂电池再利用的优点:三元锂电池在电子产品、无人机、新能源汽车等领域显示出了强劲的发展潜力,然而退役的三元锂电池处理不当产生的废液、废渣会造成生态环境污染,甚至危及人类健康。本方法通过对三元锂电池正极中的过渡金属材料进行最大化回收,具有绿色低碳、节能环保、无二次污染等特点,并兼顾经济与环保效益。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121372449B_ABST
    Figure CN121372449B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a carbon-loaded NiCoMn@(alphaNiCoMn)Se Janus low-entropy alloy-medium-entropy metal selenide heterojunction catalyst, and belongs to the technical field of waste ternary lithium battery recycling. The carbon-loaded NiCoMn@(alphaNiCoMn)Se Janus low-entropy alloy-medium-entropy metal selenide heterojunction catalyst is prepared through Joule heating and a waste ternary lithium battery recycling process. NiCoMn ions recovered from a positive electrode material of the waste ternary lithium battery are used as a transition metal source, and a Pt group metal salt is used as a noble metal source. The four metals of Pt, Ni, Co and Mn and Se elements are collectively prepared into the NiCoMn@(alphaNiCoMn)Se which is loaded on a carbon carrier through the Joule heating process. The carbon-loaded Janus structure NiCoMn@(alphaNiCoMn)Se catalyst obtained through the method is applied to a lithium air battery, so that the catalyst has a dual-function catalytic characteristic in the lithium air battery, and the electrochemical performance is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of recycling technology for waste ternary lithium batteries, specifically relating to a method for preparing a carbon-supported NiCoMn@(αNiCoMn)Se Janus low-entropy alloy-medium-entropy metal selenide heterojunction catalyst. Background Technology

[0002] Existing methods for recycling spent lithium batteries mainly include pyrometallurgical and physical methods. The core principle of pyrometallurgical processes is to remove organic matter from the battery through high-temperature incineration and reduce metal oxides to alloys. However, this process consumes a large amount of energy during high-temperature heating, resulting in high operating costs and the generation of harmful gases such as sulfur dioxide, causing severe environmental pollution. In contrast, physical methods separate different components from the battery using physical means (such as crushing and sieving), directly recovering metal foil, positive electrode materials (including nickel, cobalt, and manganese), and negative electrode graphite, without the need for high temperatures or chemical reagents. However, this method results in low purity, especially in the positive electrode material, which may contain copper and aluminum impurities, requiring secondary purification for reuse. Furthermore, it is highly dependent on the battery structure; its crushing and sorting effects are poor for complex battery structures such as stacked and pouch cells, limiting its applicability. Electrolyte treatment is also challenging, as physical processes cannot effectively remove lithium salts and organic components from the electrolyte, easily leading to electrolyte leakage and pollution.

[0003] Furthermore, current lithium-ion batteries still face significant technical bottlenecks in terms of energy density and safety. Firstly, commercially available lithium-ion batteries based on graphite anodes have reached their energy density ceiling, failing to meet the increasingly urgent demand for higher energy densities in long-range electric vehicles. While ternary lithium batteries can achieve energy densities of 300-350 Wh / kg, the atomic arrangement of the nickel-cobalt-manganese cathode materials is prone to layered structural collapse under high delithiation conditions, leading to capacity decay. Secondly, ternary materials begin to decompose and release oxygen at 200-250℃, forming a "combustion accelerant + fuel" combination with the electrolyte (ignition point 180℃), resulting in flame temperatures exceeding 1000℃ and continuous combustion. Although lithium iron phosphate batteries have a thermal runaway threshold as high as 500℃, commercially available products still emit smoke during nail penetration tests, and the probability of lithium dendrites penetrating the separator and causing internal short circuits increases exponentially with the number of cycles.

[0004] Therefore, the choice to apply recycled transition metals to lithium-air batteries is primarily due to their ultra-high theoretical energy density of 3500 Wh / kg, far exceeding that of traditional lithium-ion batteries. Secondly, the reaction mechanism of lithium-air batteries results in relatively good thermal stability; the concentration of hydroxide ions generated during operation is low, making it less prone to serious safety issues caused by heat accumulation. However, the fundamentally different operating principle of lithium-air batteries compared to lithium-ion batteries makes achieving rapid, efficient, and stable charge-discharge cycles over long periods still very challenging. Lithium peroxide generated during discharge is an insulating material, and its uneven deposition within the porous cathode can clog oxygen transport channels, leading to decreased electrode utilization. The overpotentials of oxygen reduction and oxygen evolution reactions are high; while platinum group metals can significantly reduce overpotentials, their global reserves are limited and they are expensive. Non-precious metal catalysts have low intrinsic conductivity, requiring carbon supports to enhance electron transport. Furthermore, the synthesis processes of these catalysts often involve high energy consumption and low yields, such as hydrothermal methods and conventional high-temperature annealing synthesis methods, which involve high reaction temperatures, long reaction times, and generally require large amounts of organic solvents, resulting in high costs and environmental unfriendliness.

[0005] Joule heating technology can instantly raise the temperature, shorten the reaction cycle, and avoid the heat conduction lag problem of traditional external heating. The reaction time is reduced from several hours in traditional methods to a few seconds to a few minutes. In addition, the heat from Joule heating is concentrated in the reaction system itself, resulting in high heat utilization efficiency. However, Joule heating temperature and time have a chain reaction effect on metal catalysts, from the core structure to the final performance: excessively high temperatures or long heating times can damage the active sites of the catalyst, causing metal nanoparticles to sinter and agglomerate to reduce the specific surface area or allow impurities to deposit and obscure the active sites, directly cutting off the "core interface" of the catalytic reaction; secondly, it can lead to the collapse of the catalyst's microstructure, and the imbalance of the interaction between the metal and the support can cause metal particles to fall off. Low temperatures or short heating times can lead to incomplete reactions, failing to effectively activate the metal active sites and significantly reducing the reaction rate. Even if the heating time is extended, it can only increase the conversion rate by a small amount; thirdly, the reactants that remain are prone to undergo non-target reactions (such as polymerization and cracking) at the active sites. The byproducts generated will gradually cover the active sites and block the pores of the support, hindering the contact between subsequent reactants and the active sites, forming a vicious cycle of "inefficient reaction → increased deposition", which ultimately manifests as a gradual decline in catalytic performance. Summary of the Invention

[0006] This invention discloses a method for preparing a carbon-supported NiCoMn@(αNiCoMn)Se Janus low-entropy alloy-medium-entropy metal selenide heterojunction catalyst. The method involves Joule heating and recycling of spent ternary lithium batteries to prepare the carbon-supported NiCoMn@(αNiCoMn)Se Janus low-entropy alloy-medium-entropy metal selenide heterojunction catalyst, where α is a platinum group noble metal, such as Pt, Ru, Ir, or Pd. Specifically, NiCoMn ions recovered from spent ternary lithium battery cathode materials are used as the transition metal source, supplemented by a Pt group metal salt as the noble metal source. The NiCoMn@(αNiCoMn)Se, prepared by combining Pt, Ni, Co, Mn, and Se, is loaded onto a carbon support via Joule heating. The carbon-supported Janus structure NiCoMn@(αNiCoMn)Se catalyst obtained by this method is then applied to lithium-air batteries, exhibiting dual-functional catalytic properties and significantly improved electrochemical performance.

[0007] To achieve the above objectives, the technical solution of the present invention is as follows: A method for preparing a carbon-supported NiCoMn@(αNiCoMn)Se Janus low-entropy alloy-medium-entropy metal selenide heterojunction catalyst includes the following steps: S1: Recycling of cathode materials from retired ternary lithium batteries; S2: Preparation of carbon-supported (αNiCoMn)Se precursor; S3: Preparation of carbon-supported NiCoMn@(αNiCoMn)Se Janus heterojunction alloy nanoparticle catalyst.

[0008] Preferably, step S1 includes the following specific steps: The 111-type ternary lithium battery is soaked in a 10% copper sulfate solution for 24 hours until it is fully discharged. The positive electrode material is then peeled off, cut into 5mm*5mm pieces, and soaked in an N,N-dimethylformamide solution and sonicated for 5-10 hours to dissolve the binder. The turbid solution is then centrifuged, washed, and dried to obtain a black powder rich in Li, Ni, Co, and Mn. The black powder is added to deionized water and heated to 40-60℃ with continuous stirring. Sodium bicarbonate solution is gradually added dropwise to the mixed solution to adjust the pH to 8.5-9.0, and stirring is continued for 1-2 hours. The mixture is then centrifuged to obtain a Ni, Co, and Mn carbonate precipitate free of lithium impurities. The precipitate is added to a 1M hydrochloric acid solution and stirred for 3-4 hours. The supernatant is then centrifuged to obtain a solution A containing NiCoMn ions.

[0009] Preferably, step S2 includes the following specific steps: Pt group noble metal salt solution, solution A and Se powder are added to 50-80 mL of anhydrous ethanol in a molar ratio of 1:3:4 and mixed evenly. Then, the mass of the added metal and Se powder is calculated. Then, a certain mass of carbon powder is added so that the mass of the noble metal atoms accounts for 5-10% of the total mass of the catalyst. The total volume of solution A and Pt group noble metal solution is controlled at 5-10 mL. The mixture is stirred for 4-6 h, then heated in an oil bath to 80 °C and stirred until dry. The powder is placed in a Joule heating rapid thermal shock device and heated to 950-1000 °C within 3-5 s, held for 10-15 s, and then rapidly cooled to room temperature within 5-10 s to obtain carbon-supported (αNiCoMn)Se precursor.

[0010] Preferably, step S3 includes the following specific steps: adding solution A, which corresponds to the total number of moles of NiCoMn equal to the number of moles of noble metal α, to the (αNiCoMn)Se precursor, then adding 30-50 mL of anhydrous ethanol and mixing evenly, heating in an oil bath to 80°C and stirring to evaporate to dryness, placing the powder in a Joule heating rapid thermal shock device, raising it to 800-900°C within 3 seconds, holding it at that temperature for 5 seconds, and then rapidly cooling it to room temperature within 5 seconds to obtain the carbon-supported NiCoMn@(αNiCoMn)Se Janus heterojunction structure alloy nanoparticle catalyst.

[0011] The beneficial effects of the method for preparing a carbon-supported NiCoMn@(αNiCoMn)Se Janus low-entropy alloy-medium-entropy metal selenide heterojunction catalyst of the present invention are as follows: (1) Advantages of reusing waste ternary lithium batteries: Ternary lithium batteries have shown strong development potential in fields such as electronic products, drones, and new energy vehicles. However, improper disposal of retired ternary lithium batteries can cause environmental pollution and even endanger human health. This method maximizes the recovery of transition metal materials in the positive electrode of ternary lithium batteries, and has the characteristics of being green and low-carbon, energy-saving and environmentally friendly, and free from secondary pollution, while taking into account both economic and environmental benefits.

[0012] (2) Advantages of Joule heating process: Conventional high-temperature annealing can usually promote the rearrangement of metal atoms and the interaction of dd orbitals, but its low heating efficiency leads to a long overall annealing cycle, limited heating and cooling rates, and easy particle agglomeration and uneven size distribution, which affects the catalytic activity of the reaction process. This method uses rapid Joule thermal shock to uniformly anchor alloy nanoparticles on the surface of carbon matrix. The extremely fast heating and cooling rate and short-term ultra-high temperature holding of this technology can achieve uniform particle distribution, which can fully stimulate catalytic activity, thereby improving catalytic ability and stability.

[0013] (3) Advantages of medium-entropy alloys: Most single-metal transition metal selenides have semiconductor or half-metal properties and poor conductivity, which cannot meet the requirements of efficient electrocatalysis or high-rate energy storage scenarios. Moreover, the active sites that can participate in the reaction on the surface are mainly concentrated at the edges or defects, and the catalytic activity of the basal surface atoms is extremely low, resulting in a limited overall active site density. Platinum group metals have extremely high catalytic activity as catalysts, but they are expensive and resources are limited. The rapid Joule thermal shock technology used in this method to prepare αNiCoMn gives it abundant defects due to the random distribution of the three transition metal elements, endowing it with unique properties and optimal electronic structure, which will greatly improve the oxygen reduction (ORR) / oxygen evolution (OER) performance. Secondly, αNiCoMn alloys directly reduce the Pt content, significantly reducing the cost of precious metals. The alloying effect can also change the d-band center of Pt, enhancing its adsorption / desorption capacity for reactant molecules. This electronic regulation effect improves the catalytic activity of each Pt atom, further reducing the actual amount of Pt used.

[0014] (4) Advantages of Janus heterojunctions: Electron interactions at the heterostructure interface involve electron conduction. Electrons and holes rearrange and focus at different sites in the heterostructure catalyst to form polarized interfaces. Charge reconstruction generates a local nucleophilic region and an electrophilic region near the heterostructure interface. This facilitates rapid charge transfer at the interface and enhances the overall electron transport capability of the heterostructure. This method prepares NiCoMn@(αNiCoMn)Se heterostructure catalysts via Joule heating. Compared to single-component catalysts, heterostructures can achieve synergistic effects, fine local electronic structure control, and efficient transition of intermediate metastable phases, thereby significantly improving the kinetics and electrochemical performance of bifunctional catalytic reactions.

[0015] (5) This method is universal. By changing the type of noble metal α salt (α = platinum salt, iridium salt, ruthenium salt, rhodium salt), a series of carbon-supported NiCoMn@(αNiCoMn)Se heterojunction catalysts can be obtained.

[0016] (6) The raw materials for this method are widely available, inexpensive, simple to synthesize, highly reproducible, and highly applicable, making it suitable for industrial-scale production. Attached Figure Description

[0017] Figure 1 This is a scanning electron microscope image of a carbon-supported NiCoMn@(αNiCoMn)Se Janus heteropolymer gold nanoparticle catalyst. Figure 2 Transmission electron microscopy image of carbon-supported NiCoMn@(αNiCoMn)Se Janus heteropolymer gold nanoparticle catalyst: Figure 3The full charge-discharge performance curves of a lithium-air battery with a carbon-supported NiCoMn@(αNiCoMn)Se Janus heteropolymer-bonded gold nanoparticle catalyst are shown. Figure 4 This is a rate performance diagram of the carbon-supported NiCoMn@(αNiCoMn)Se Janus heteropolymer gold nanoparticle catalyst. Detailed Implementation

[0018] The following description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

[0019] The following embodiments can be understood as illustrating a part of the structure or method of the present invention individually, or as combining the embodiments to explain the broader structure or method of the present invention.

[0020] Example 1: A method for preparing a carbon-supported NiCoMn@(αNiCoMn)Se Janus low-entropy alloy-medium-entropy metal selenide heterojunction catalyst includes the following steps: S1: Recycling of cathode materials from retired ternary lithium batteries; S2: Preparation of carbon-supported (αNiCoMn)Se precursor; S3: Preparation of carbon-supported NiCoMn@(αNiCoMn)Se Janus heterojunction alloy nanoparticle catalyst.

[0021] Example 2: Step S1 includes the following specific steps: The 111-type ternary lithium battery is soaked in a 10% copper sulfate solution for 24 hours until it is fully discharged. The positive electrode material is then peeled off, cut into 5mm*5mm pieces, and soaked in an N,N-dimethylformamide solution and sonicated for 5-10 hours to dissolve the binder. The turbid solution is then centrifuged, washed, and dried to obtain a black powder rich in Li, Ni, Co, and Mn. The black powder is added to deionized water and heated to 40-60℃ with continuous stirring. Sodium bicarbonate solution is gradually added dropwise to the mixed solution to adjust the pH to 8.5-9.0, and stirring is continued for 1-2 hours. The mixture is then centrifuged to obtain a Ni, Co, and Mn carbonate precipitate free of lithium impurities. The precipitate is added to a 1M hydrochloric acid solution and stirred for 3-4 hours. The supernatant is then centrifuged to obtain a solution A containing NiCoMn ions.

[0022] Example 3: Step S2 includes the following specific steps: Pt group noble metal salt solution, solution A and Se powder are added to 50-80 mL of anhydrous ethanol in a molar ratio of 1:3:4 and mixed evenly. Then, the mass of the added metal and Se powder is calculated. Then, a certain mass of carbon powder is added so that the mass of the noble metal atoms accounts for 5-10% of the total mass of the catalyst. The total volume of solution A and Pt group noble metal solution is controlled at 5-10 mL. Stir for 4-6 h, then heat in an oil bath to 80 °C and stir to dryness. Place the powder in a Joule heating rapid thermal shock device and raise it to 950-1000 °C within 3-5 s, hold it at that temperature for 10-15 s, and then rapidly cool it to room temperature within 5-10 s to obtain carbon-supported (αNiCoMn)Se precursor.

[0023] Example 4: Step S3 includes the following specific steps: Add solution A, which corresponds to the total number of moles of NiCoMn equal to the number of moles of noble metal α, to the (αNiCoMn)Se precursor, then add 30-50 mL of anhydrous ethanol and mix evenly. Heat the mixture in an oil bath to 80°C and stir until dry. Place the powder in a Joule heating rapid thermal shock device and raise it to 800-900°C within 3 seconds, hold it at that temperature for 5 seconds, and then rapidly cool it to room temperature within 5 seconds to obtain the carbon-supported NiCoMn@(αNiCoMn)Se Janus heterojunction structure alloy nanoparticle catalyst.

[0024] Working principle of the invention: like Figure 1-4 As shown: 1. The core advantage of using sodium bicarbonate in the wet process recycling of ternary lithium battery cathodes lies in its precise adaptation to key process requirements and its multi-dimensional benefits: First, it is a highly efficient and selective lithium precipitation reagent. In the recycling process, it reacts with lithium ions in the leachate to form lithium carbonate precipitate, which does not easily adsorb other metal ions such as nickel, cobalt, and manganese. As a weakly alkaline substance, it can gently adjust the pH value of the leaching system, avoiding premature precipitation of nickel, cobalt, and manganese ions due to the use of strong alkalis. In addition, sodium bicarbonate has extremely low toxicity, and the byproducts after the reaction are mostly carbon dioxide and water, with no harmful pollutant emissions, significantly reducing environmental treatment costs. Moreover, it is inexpensive and readily available, making it more economical than dedicated chemical lithium precipitation agents. Furthermore, the generated lithium carbonate precipitate particles are relatively large and easy to filter, resulting in high overall process efficiency. 2. Medium-entropy alloy selenides can systematically solve a series of problems through the synergistic characteristics of "alloying + selenide". First, by forming stronger metal-selenium chemical bonds with the alloying elements, selenium dissolution in the electrolyte is reduced, thus improving corrosion resistance. Then, the lattice distortion introduced by the alloy increases the activation energy of the active phase transition, and the strong bonding force of intermetallic compounds anchors the crystal structure. Furthermore, the high-melting-point components in the alloy create steric hindrance, limiting the migration and aggregation of nanoparticles and maintaining the exposure of active sites. Overall, transition metal alloy selenides can achieve a balance between activity and stability by controlling the alloy composition and precisely adapting to the stability requirements of different catalytic scenarios.

[0025] 3. Transition metal selenides suffer from poor intrinsic conductivity, while noble metals possess excellent conductivity. Transition metals also exhibit good electronic conductivity. When these two are alloyed, their respective metallic bond conductivity is not disrupted, thus laying the foundation for high catalyst conductivity. Alloying noble metal α with transition metals Ni, Co, and Mn to form αNiCoMn medium-entropy alloys offers the primary advantage of synergistically enhancing catalytic activity through electronic and geometric effects. Electrons from the 3d orbitals of transition metals transfer to the 5d orbitals of noble metals, reducing the d-band center of noble metals and optimizing the adsorption strength of reaction intermediates such as ORR. Simultaneously, the introduction of transition metal atoms compresses the bond length of noble metals, increasing the density of active sites, resulting in a mass activity several times that of pure noble metal catalysts. Secondly, the significantly reduced proportion of noble metals in the alloy effectively lowers raw material costs, while maintaining high dispersion without complex support modifications further simplifies the process. In addition, medium-entropy alloys have both good stability and compatibility with large-scale synthesis. The alloy lattice can suppress the dissolution and agglomeration of noble metals during the cycling process, and can be adapted to electrode preparation processes in other battery scenarios, achieving the comprehensive advantages of "high activity, low cost, high stability and reproducibility", making it a high-efficiency optimization direction for noble metal catalysts.

[0026] 4. The core advantage of Janus heterojunction catalysts in the field of electrocatalysis stems from their unique "bifacial heterogeneity." This asymmetric characteristic creates sites with different chemical environments and active centers on both sides of the catalyst surface. These sites can be adapted to different stages of multi-step electrocatalytic reactions or simultaneously catalyze complementary reactions, fundamentally solving the compatibility contradiction of a single active site. At the same time, the heterojunction interface forms a built-in electric field due to the difference in electronegativity of the components, driving the directional transfer of electrons and reconstructing the surface electronic structure. By regulating the d-band center to optimize the adsorption intensity of reaction intermediates, the reaction energy barrier is significantly reduced and the catalytic kinetic rate is improved, achieving a "1+1>2" effect. The anchoring effect of the interfacial chemical bonds and the introduction of highly conductive components effectively inhibit catalyst agglomeration, dissolution, and other failure behaviors, and also construct continuous electron transport channels, achieving a synergistic balance between activity and stability. In addition, through flexible control of components, thickness, or doping, this type of catalyst can also be adapted to various electrocatalytic scenarios such as hydrogen evolution, oxygen evolution, and oxygen reduction, achieving multifunctional integration, greatly simplifying catalytic system design, and reducing application costs.

[0027] 5. The heating and cooling rates, heating temperature, and holding time of Joule heating rapid thermal shock technology all have different and varying degrees of influence on the materials. Therefore, the adaptability of Joule heating parameters to the preparation of different materials is particularly important. The Joule heating temperature and time in this process can, to a certain extent, prevent particle sintering or changes in chemical state, maintain its high specific surface area and active chemical state, and maintain the balanced interaction between the metal and the support. Ultimately, it can achieve optimal catalytic performance, while also having high energy utilization efficiency, avoiding energy waste caused by improper temperature and time, balancing catalytic effect and economic efficiency, and maximizing the application value of metal catalysts.

Claims

1. A method for preparing a carbon-supported NiCoMn@(αNiCoMn)Se Janus low-entropy alloy-medium-entropy metal selenide heterojunction catalyst, characterized in that, Includes the following steps: S1: Recycling of cathode materials from retired ternary lithium batteries; S2: Preparation of carbon-supported (αNiCoMn)Se precursor; where α is a platinum group noble metal, one of Pt, Ru, Ir, and Pd; S3: Preparation of carbon-supported NiCoMn@(αNiCoMn)Se Janus heterojunction alloy nanoparticle catalyst; Step S1 includes the following specific steps: Immerse the 111-type ternary lithium battery in a 10% copper sulfate solution for 24 hours until it is fully discharged. Then peel off the positive electrode material, cut it into 5mm×5mm pieces, and immerse it in an N,N-dimethylformamide solution for ultrasonication for 5-10 hours to dissolve the binder. Then, centrifuge, wash, and dry the turbid solution to obtain a black powder rich in Li, Ni, Co, and Mn. Add the black powder to deionized water and heat to 40-60℃ with continuous stirring. Gradually add sodium bicarbonate solution to the mixed solution, adjust the pH to 8.5-9.0, and continue stirring for 1-2 hours. Then, centrifuge to obtain a Ni, Co, and Mn carbonate precipitate free of lithium impurities. Add the precipitate to a 1M hydrochloric acid solution, stir for 3-4 hours, centrifuge, and take the supernatant to obtain a solution A containing NiCoMn ions. Step S2 includes the following specific steps: Platinum group noble metal salt solution, solution A and Se powder are added to 50-80 mL of anhydrous ethanol in a molar ratio of 1:3:4 and mixed evenly. Then, the mass of the added metal and Se powder is calculated. Then, a certain mass of carbon powder is added so that the mass of noble metal atoms accounts for 5-10% of the total mass of the catalyst. The total volume of solution A and platinum group noble metal solution is controlled at 5-10 mL. The mixture is stirred for 4-6 h, then heated in an oil bath to 80 °C and stirred until dry. The powder is placed in a Joule heating rapid thermal shock device and heated to 950-1000 °C within 3-5 s, held for 10-15 s, and then rapidly cooled to room temperature within 5-10 s to obtain carbon-supported (αNiCoMn)Se precursor. Step S3 includes the following specific steps: Add solution A, which corresponds to the total number of moles of NiCoMn equal to the number of moles of α, to the (αNiCoMn)Se precursor, then add 30-50 mL of anhydrous ethanol and mix evenly. Heat the mixture in an oil bath to 80°C and stir until dry. Place the powder in a Joule heating rapid thermal shock device and raise it to 800-900°C within 3 seconds, hold it at that temperature for 5 seconds, and then rapidly cool it to room temperature within 5 seconds to obtain the carbon-supported NiCoMn@(αNiCoMn)Se Janus low-entropy alloy-medium-entropy metal selenide heterojunction catalyst.

Citation Information

Patent Citations

  • Carbon-coated Janus structural metal / metal oxide composite catalyst as well as preparation and application thereof

    CN109985631A